1989
DOI: 10.1111/j.1745-4557.1989.tb00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cooking Conditions and Post‐preparation Procedures on the Quality of Battered Fish Portions

Abstract: The effects of different cooking conditions and postpreparation handling on quality of batteredfish portions for fast food services were investigated. As the frying temperature increased from 300 to 400°F (149-204"C), the cooking time of battered fish portions decreased from 276 to 202 s. Crude lipid content in the batter decreased as the temperature of the frying oil increased. Holding times (10, 20 min) affected crude lipid contents of the batter depending on the cooking temperature and were lower than an un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

1994
1994
2016
2016

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 4 publications
(2 reference statements)
0
1
0
2
Order By: Relevance
“…Increase in cooking temperature prevented more fat absorption. Flick et al (1989) reported that fat content in battered fish portions decreased with increase in temperature. Table 3 shows effect of cooking methods and cooking temperatures on mineral composition of anchovy.…”
Section: Resultsmentioning
confidence: 99%
“…Increase in cooking temperature prevented more fat absorption. Flick et al (1989) reported that fat content in battered fish portions decreased with increase in temperature. Table 3 shows effect of cooking methods and cooking temperatures on mineral composition of anchovy.…”
Section: Resultsmentioning
confidence: 99%
“…Los factores que influyen en la usualmente menor alteración del contenido lipídico de los alimentos fritos de origen animal frente a los de origen vegetal son: una menor cantidad de agua inicial generalmente, un mayor contenido graso y diferencias notables en cuanto a la textura y estructura celular (Makinson et al, 1987). Flick et al (1989) estudiaron el efecto de la temperatura en la absorción de grasa en porciones de pescado rebozado y concluyeron que al aumentar la temperatura de fritura disminuía el contenido en grasa de la capa de rebozado.…”
Section: Estudio De La Fracción Lipídica En Distintos Productos Fritosunclassified
“…Los factores que influyen en la usualmente menor alteración del contenido lipídico de los alimentos fritos de origen animal frente a los de origen vegetal son: una menor cantidad de agua inicial generalmente, un mayor contenido graso y diferencias notables en cuanto a la textura y estructura celular (Makinson et al, 1987). Flick et al (1989) estudiaron el efecto de la temperatura en la absorción de grasa en porciones de pescado rebozado y concluyeron que al aumentar la temperatura de fritura disminuía el contenido en grasa de la capa de rebozado.Como se ha explicado al principio de este apartado, actualmente todos estos productos rebozados se preparan a escala industrial y se comercializan en congelación, por lo que el consumidor solamente ha de someterlos a una fritura Introducción 25 doméstica final. Esto supone una serie de operaciones en la industria, como son una prefitura industrial del producto recién rebozado, seguida de una congelación que se mantendrá durante el transporte, venta, etc... hasta su consumo.…”
unclassified